The man in the street: Papers on American topics - Nicholson, Meredith, 1866-1947 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Man in the Street: Papers on American Topics" by Meredith Nicholson is a collection of essays written in the early 20th century. The work reflects on various facets of American life, including literature, politics, and society, offering insights into the character of the average American citizen. Nicholson's writing captures a range of topics that aim to foster a greater understanding of the intricate tapestry of American culture. The opening of the collection sets the stage for Nicholson's exploration of themes surrounding American identity and small-town life. In the first essay, titled "Let Main Street Alone!", he engages in a discourse on the virtues and idiosyncrasies of small-town America, arguing against the critical portrayals often seen in larger cities and literary works, such as Sinclair Lewis's "Main Street." He emphasizes the pride and distinctiveness found in smaller communities, encouraging a deeper appreciation for the lives and struggles of ordinary citizens. The writing is both reflective and conversational, inviting readers to consider the rich tapestry of American experiences through Nicholson$1 (Bs lens. (This is an automatically generated summary.)s
Let Main Street alone! -- James Whitcomb Riley -- The cheerful breakfast table -- The Boulevard of Rogues -- The open season for American novelists -- The church for honest sinners -- The second-rate man in politics -- The lady of Landor Lane -- How, then, should Smith vote? -- The poor old English language.
Release date is 2023-01-01
D A Alexander, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by Cornell University Digital Collections)
Keywords: American essays -- 20th century